THE DEMOCTRATIZATION OF EDUCATIONAL SYSTEM IN ISLAMIC BOARDING SCHOOL; CASE STUDY IN AL-MUNAWIR ISLAMIC BOARDING SCHOOL IN KRAPYAK YOGYAKARTA (DEMOKRATISASI SISTEM PENDIDIKAN PESANTREN; Studi Kasus Pondok Pesantren Al-Munawwir Krapyak Yogyakarta) - IIS ARIFUDIN (al-Afkar, Journal For Islamic Studies, 2019)
The research aims to investigate: (1) implementation of democtratization of educational system in islamic boarding school; (2) the factor of prosponent and inhibit in implementing of democtratization of educational system in boarding school; and (3) the prospect of democtratization of educational system in boarding school to shape civil society. The research was qualitatif approach by using case study. Research subject are headmaster of boarding school and student. The data were colected by observation, interview, and documentation. The data were analyzed desciptively. The results showet that: The first; implementation of the democratization of the educational system in Islamic boarding schools in the form of: 1) to establish an open attitude through a process approach in teaching. 2) to establish collective leadership. 3) There is no punishment system for students who violated the regulation, but by inculcating self-awareness. 4) There is freedom for student of boarding school to have communication devices / mobile phones. 5) the headmaster of boarding school gave concessions to student to look for general knowledge outside the boarding school. Second; Supporting Factors: education of Humanist-religious, enthusiasm and religious motivation, sincerity, and autonomy and independence. While the inhibiting factors include: Eliteism in religion. Barakah tradition and total obedience was wrong. Third; The prospect of democratization educational system in boarding school to shape civil society. Civil society was the form of society that was based on religion as a source of morality, inspiration and action in order of social life for social togetherness to live peacefully, democratic and tolerant, so that shape an ethical society, egalitarian and civilization. Penelitian ini bertujuan untuk menginvestigasi: (1) pelaksanan demokratisasi sistem pendidikan di Pondok Pesantren; (2) faktor pendukung dan penghambat pelaksanaan demokratisasi sistem pendidikan di pondok pesantren; dan (3) prospek demokratisasi sistem pendidikan pondok pesantren dalam mewujudkan masyarakat madani. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Subyek penelitianya adalah pengasuh pesantren dan santri. Metode pengumpulan datanya dengan observasi, wawancara dan dokumentasi. Metode analisis data bersifat deskriptif. Hasil penelitianya menunjukan: Pertama; Pelaksanaan demokratisasi sistem pendidikan di pondok pesantren berupa: 1) Pembentukan sikap terbuka melalui pendekatan proses dalam pengajaran. 2) Membentuk kepemimpinan kolektif. 3) Tidak ada sistem ta’zir (hukuman) bagi santri yang melanggar qanun (peraturan), tapi dengan penanaman kesadaran diri. 4) Adanya kebebasan bagi santri untuk memiliki alat komunikasi/handphone. 5) Pengasuh memberikan kelonggaran kepada santri untuk mencari ilmu pengetahuan umum di luar pondok pesantren. Kedua; Faktor Pendukung: Pendidikan humanis-religius, semangat dan motivasi agama, keikhlasan, dan otonomi serta kemandirian. Sedangkan faktor penghambatnya antara lain: Elitisme dalam agama. Tradisi barokah dan kepatuhan total yang salah. Ketiga; Prospek demokratisasi sistem pendidikan pesantren dalam mewujudkan masyarakat madani. Masyarakat madani merupakan bentuk masyarakat yang didasarkan agama sebagai sumber moral, inspirasi dan aksi dalam tatanan kehidupan bermasyarakat atas kebersamaan sosial untuk hidup secara damai, penuh demokratis dan toleransi, sehingga terwujud masyarakat etis, egaliter dan berbudaya. Karena masyarakat madani tidak akan terwujud tanpa proses transmisi kebudayaan yang di dalamnya sangat berperan fungsi pendidikan.